Improved livelihoods and food security for over 2000 households from rehabilitation of a degraded watershed is leading to scaling out of the model to other watersheds in Ethiopia - CGIAR Research Program on Water, Land and Ecosystems (2021)
A once degraded and unproductive Ethiopian watershed has been restored through an integrated landscape management approach. Hillside terracing and the implementation of contour farming practices have reduced soil erosion and increased groundwater recharge. In upstream hillslopes, potato farming now enables youth to earn more cash. In downstream areas, the irrigable area has been increased. Productivity and food security have therefore greatly improved, and lessons learnt are being applied to degraded land in at least 20 additional districts.